Low temperature magnetic properties and stress effects in glassy Fe-B alloys: the eutectic region - Beznosov, A. B.; Fertman, E. L.; Eremenko, V. V.; Desnenko, V. A.; Bengus, V. Z. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1999)
The magnetic properties of glassy Fe100-xBx (x= 14, 16, 17, 20) alloys under a low mechanical stress (up to 68 MPa) at temperatures 10-300 K, in magnetic fields up to 40 Oe, have been studied. Low temperature anomalies of magnetic susceptibility, as well as substantial differences in the effects of stresses on the low field magnetic characteristics of alloys with various boron contents, have been revealed. The eutectic alloy Fe83B17 was found to be the least sensitive to applied stresses, magnetic fields, and temperature changes: it possesses the lowest magnetic induction in the reversibility fields region and the highest local anisotropy fluctuations. The hypoeutectic Fe84B16 alloy is the most sensitive to applied stresses at room temperature, but its sensitivity substantially reduces with increasing load, as well as with decreasing temperature. The results obtained reflect the special character of the alloys electronic structure at the eutectic point.